Indonesia-China relationship: The political identity and social conflict in Padang, West Sumatera - Indonesia - Fahmi, Reza (Technium Social Sciences Journal, 2020)
The ups and downs of relations between Indonesia and China in West Sumatra have been going on for a long time and have even given deep wounds to the victims of the conflict. Identity politics (indigenous and non-indigenous) have also provided a separate partition in acculturation and assimilation of the culture of Chinese or Chinese (non-indigenous) descendants in Padang, West Sumatra. Research objectives: (1) Describe identity politics in Padang, West Sumatra. (2) Describes social conflict between indigenous and non-indigenous people in Padang, West Sumatra. (3) Describe the influence of identity politics and social strife in Padang, West Sumatra. The research uses a quantitative approach. The population in the study was 360 people—methods of collecting data through psychological scales and interviews. The sampling technique used is simple random sampling. Data analysis techniques use simple regression. The results of this study found no influence of identity politics on social conflict in the city of Padang.